IMPLEMENTATION OF THE 2020 SUMENEP VISIT PROGRAM IN INCREASING POTENTIAL TOURISM IN SUMENEP DISTRICT - Toyu, Moh (JURNAL SETIA PANCASILA, 2023)
The Visit Sumenep program is the flagship program of the Sumenep district government which has been launched since 2020 and is packaged with two main menus, namely the tourist destination menu which contains tourism promotions in Sumenep district including nature tourism, marine tourism, cultural tourism and culinary tourism and menus that the second is the major events that have been held since 2017. The purpose of this research is to find out how the implementation of the 2020 Visit Sumenep program is in coastal tourism areas and how the impact of the Visit Sumenep implementation on the community's economic sector. This research is a field research with a phenomenological approach. The datacollection technique uses interview, observation, and documentation techniques. The results of this study indicate that, from each Sumenep visit event which was held from the end of 2017 and throughout 2020 there were no special events related to the development of the tourism potential of Lombang Beach. Nevertheless, the 2020 Sumenep visit has the aim ofincreasing tourist visits in Sumenep, including Lombang Beach. this is evidenced by the increasing number of tourists, both local tourists and foreign tourists visiting Lombang Beach in 2020..